Pengaruh Slow Music Terhadap Kemampuan Menyimak Bahasa Inggris - Tities Hijratur Rahmah; Yahmun Yahmun; Artifa Sorraya (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2023)
There are various kinds of strategies and methods in language learning. Music is one the strategy that can be applied. The aim of this research is to determine the effect of slow music on students' English listening skills. The method of this research is Classroom action research. The subjects of this research were 27 students of the History and Sociology Department of IKIP Budi Utomo. The results of this research explain that the application of slow music has a significant and positive impact on listening ability for the students of History and Sociology Department of IKIP Budi Utomo. Students' response and activeness in learning is very good, their accuracy in pronouncing the words, understanding native speech, and their English vocabulary have increased. Students become more focused in learning because they participate in the teaching and learning process happily without feeling afraid or burdened.